Flexible Learning during the Covid-19 Pandemic: The Experiences and Challenges of Undergraduate Psychology Students in the University of Bamenda - Dr. Nji Roland Angu; Dr Ambei Moses Chu (International Journal on Integrated Education, 2021)
Flexible Learning is a pedagogical approach that provides learners with a multitude of choices ranging from when, where and how learning occurs with the use of technologies. This study aimed at examining flexible learning during the Covid 19 Pandemic. More specifically, it investigated the experiences and challenges of online learning of first, second and third year undergraduate Psychology Students of the University of Bamenda during the Covid 19 pandemic. Vygotsky’s (1978) Theory of social constructivism provided the theoretical underpinnings of the study. The study made use of a Sequential explanatory design whereby fifty (50) male and female first, second and third year undergraduate Psychology students responded to both structured and unstructured questionnaire. The questionnaire was structured on a four point Likert scale format. Data analysis made use of frequencies and percentages, as well as thematic analysis for the open ended items. Findings indicate that the communication infrastructures put in place for online learning are very bad and unreliable to sustain online learning. The study also concluded that the online learning resources at the disposal of students are not suitable enough. Based on the findings, recommendations were made to the government, as well as educational authorities in the University of Bamenda to put in place structures and facilities to promote online learning.